Seasonal Occurrence of Immature Mosquitoes in Swimming Pools in Buenos Aires, Argentina - Fischer, Sylvia Cristina (2010)
The seasonal variation in the density of swimming pools and the occurrence of immature mosquitoes in these habitats were studied in the temperate city of Buenos Aires, Argentina. The density of swimming pools was highest in the summer (6.0 pools/ha) when temporal pools predominated; it was lowest in the winter (0.9 pools/ha) when only permanent pools were recorded. The presence of immature stages of mosquitoes was mainly associated with the lack of use and maintenance of the pools in the fall season, when temporal pools were still assembled but not intensively used. Seven mosquito species were recorded, among which Culex pipiens and Culex apicinus were the most frequent.